Control of phenolic oxidation in the in vitro culture of Astronium urundeuva (M. Allemão) Engl. - Silva, Leonardo Máximo; Oliveira, Leandro Silva de; Nogueira, Ariane da Silva; Souza, Nayara dos Santos de; Jorge, Nicole Vieira; Honorato, Glenda Araújo de Souza; Silva, Leovandes Soares da (Brazilian Journal of Production Engineering, 2023)
Astronium urundeuva (Aroeira-do-sertão) is a Brazilian native species with silvicultural potential for logging. In the in vitro cultivation of the species, difficulties such as phenolic oxidation have been observed, mainly from explants collected from adult matrix trees. Thus, the explants originating from seeds are an alternative for the propagation of the species to minimize oxidation. In this context, the study aimed to evaluate the action of ascorbic acid, activated charcoal, and polyvinylpyrrolidone in controlling phenolic oxidation in the in vitro culture of A. urundeuva. Apical shoots obtained from seedlings of A. urundeuva germinated in vitro were used as explants. They were cultivated in MS50% culture medium plus ascorbic acid (0.2; 0.4; 0.6, and 0.8 mg.L-1) and activated charcoal (3.0; 6.0; 9.0, and 12 g.L-1) and polyvinylpyrrolidone (0.5; 1.0; 1.5 and 2.0 g.L-1). After in vitro culture, ascorbic acid, activated charcoal, and PVP at concentrations of 0.2 mg.L-1, 12 g.L-1 and 1.5 g.L-1, respectively, were effective in controlling phenolic oxidation. At this concentration, activated charcoal completely regulated the phenolic oxidation of the seedlings. The results of this work demonstrate the feasibility of antioxidants in minimizing the effects of phenolic oxidation, especially with the use of activated charcoal, and open perspectives for further studies of micropropagation of A. urundeuva, both in juvenile and adult genetic materials, contributing to its conservation and assisting in the genetic improvement of the species.
Keywords: Aroeira do sertão; Juvenile shoots; Antioxidant